2021
DOI: 10.1098/rspb.2020.2734
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor transitions in the potential energy landscape-dominated regime

Abstract: To traverse complex three-dimensional terrain with large obstacles, animals and robots must transition across different modes. However, the most mechanistic understanding of terrestrial locomotion concerns how to generate and stabilize near-steady-state, single-mode locomotion (e.g. walk, run). We know little about how to use physical interaction to make robust locomotor transitions. Here, we review our progress towards filling this gap by discovering terradynamic principles of multi-legged locomotor transitio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 93 publications
(234 reference statements)
0
18
0
Order By: Relevance
“…for body pitch < −90°; the full landscape maybe visualized using data and code provided (Othayoth and Li, 2021).…”
Section: Model Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…for body pitch < −90°; the full landscape maybe visualized using data and code provided (Othayoth and Li, 2021).…”
Section: Model Definitionmentioning
confidence: 99%
“…A recent potential energy landscape approach to locomotor transitions (Othayoth et al, 2021(Othayoth et al, , 2020 provides a modeling framework to understand how propelling and perturbing appendages together contribute to strenuous ground self-righting. A previous study modeling ground self-righting of turtles in two dimensions (the transverse plane in which the body rolls) suggested that, when trapped in a gravitational potential energy well, modest kinetic energy from perturbing appendages (legs and neck) helps overcome the small potential energy barriers (Domokos and Várkonyi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of how multi-legged animals adapt their gaits depending on terrain properties is addressed by Othayoth et al . [ 13 ] in their study, ‘Locomotor transitions in the potential energy landscape-dominated regime’. They investigate ‘terradynamic’ principles of locomotor transitions, using simplified model systems representing distinct challenges in complex three-dimensional terrains, for instance squeezing through pillars and flexible beams, crossing gaps, going-over steps or self-righting after flipping over.…”
Section: Terrestrial Locomotion Robotics and Modellingmentioning
confidence: 99%
“…where m is the total mass of the animal or robot, g is gravitational acceleration, zCoM is center of mass height from the ground. To determine the robot's center of mass, we used a CAD model of the robot (Figures 2A, Because the animal or robot did not pitch backward significantly, in the figures we do not show landscape for body pitch < −90°; the full landscape maybe visualized using data and code provided (Othayoth and Li, 2021).…”
Section: Model Definitionmentioning
confidence: 99%
“…Data from (Li et al, 2019). A recent potential energy landscape approach to locomotor transitions (Othayoth et al, 2021(Othayoth et al, , 2020) 97 provides a modeling framework to understand how propelling and perturbing appendages together 98 contribute to strenuous ground self-righting. A previous study modeling ground self-righting of turtles in 99 two dimensions (the transverse plane in which the body rolls) suggested that, when trapped in a gravitational potential energy well, modest kinetic energy from perturbing appendages (legs and neck) helps overcome the small potential energy barriers (Domokos and Várkonyi, 2008).…”
Section: Introductionmentioning
confidence: 99%